2017
DOI: 10.1017/s0714980817000381
|View full text |Cite
|
Sign up to set email alerts
|

Educator Readiness to Improve Gerontological Curricula in Health and Social Service Education

Abstract: This study investigated the state of gerontology content in health and social service education programs in Ontario, and readiness indicators for change among administrators and faculty. We conducted a survey of teaching faculty (n = 100) and deans or directors (n = 56) of 89 education programs, which revealed mixed evidence on readiness for change. Most respondents thought their programs were adequate but needed enhancement. However, they were unaware of published gerontological competencies with which to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…Canadian gerontological experts have developed gerontological competencies for nursing programs [ 34 ], and professional gerontological nursing standards and competencies to meet best practice expectations [ 35 ]. Unfortunately, these competencies have not been consistently incorporated into accreditation processes or curriculum revision initiatives and Canadian health and social service faculty are often unaware of published gerontological competencies that could aid them in curricular evaluation and optimization [ 36 ]. Barriers to integrating gerontological competencies include insufficient faculty expertise in gerontology and little recognition that gerontological competencies are needed [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian gerontological experts have developed gerontological competencies for nursing programs [ 34 ], and professional gerontological nursing standards and competencies to meet best practice expectations [ 35 ]. Unfortunately, these competencies have not been consistently incorporated into accreditation processes or curriculum revision initiatives and Canadian health and social service faculty are often unaware of published gerontological competencies that could aid them in curricular evaluation and optimization [ 36 ]. Barriers to integrating gerontological competencies include insufficient faculty expertise in gerontology and little recognition that gerontological competencies are needed [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these competencies have not been consistently incorporated into accreditation processes or curriculum revision initiatives and Canadian health and social service faculty are often unaware of published gerontological competencies that could aid them in curricular evaluation and optimization [ 36 ]. Barriers to integrating gerontological competencies include insufficient faculty expertise in gerontology and little recognition that gerontological competencies are needed [ 36 ]. If ageism was acknowledged, there would be a stronger impetus for implementing these competencies, thereby better serving older Canadians.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the educational preparation for RNs does not always address the different facets of the RN role. Despite standardized expectations for all baccalaureate nursing programs (Canadian Association of Schools of Nursing, 2015), McCleary, Boscart, Donahue, and Harvey (2014) and Hirst, Lane, and Stares (2012) found that gerontological content is insufficient in most BScN curriculum across the country. Furthermore, many new nursing graduates do not have the capabilities required to take on a leadership role, regardless of care setting, upon graduation (Bowers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated earlier, Koskinen et al's (2015) review suggested gerontology competencies could facilitate improvements to gerontological content in nursing curricula. Scholars examining how healthcare professionals incorporate content to facilitate gerontological competence suggested that educator gerontological expertise is necessary to bring these competencies into the curricula in a meaningful way (McCleary et al, 2017).…”
Section: Discussionmentioning
confidence: 99%